Establishing an evaluation index system of nursing quality for clinical drug trials: A Delphi study - Junyi Chen; Huiyu Zhou; Qingxiu Mai; Shuping Chen; Qingyin Liu; Mengyun Shi; Yunni Lin; Lihong Yan; Meiyu Li; Suiwen Ye; Herui Yao (Wiley, 2023)
Abstract Aims To construct a quality evaluation index system for clinical drug trials nursing management and obtain the weight of all indicators. Design A mixed‐method research design with a quantitative component was used, primarily qualitative. Methods Through a literature review and semi‐structured interview, an expert consultation questionnaire on the quality of nursing evaluation indicators for clinical drug trials was developed in April 2021. Eighteen experts in clinical drug trial nursing, medical, and pharmacy conducted 2 rounds of consultation according to the Delphi method to determine the indicators for evaluating the quality of clinical drug trial nursing. The weights of each indicator were determined using analytic hierarchical analysis. Results The established quality evaluation system of clinical drug trial nursing mainly includes 3 first‐level indicators, 12 second‐level indicators, and 59 third‐level indicators. The positive coefficients of the two rounds of expert consultation were 90%-100%, and the authority coefficients were 0.831 and 0.885, respectively; the coordination coefficients were 0.189 and 0.214, respectively. The consulting results and weight settings are reliable. The evaluation index system we constructed is in line with the characteristics of the clinical drug trial nursing profession, with clear index levels and strong clinical operability, which can provide a reference for the assessment, monitoring and improvement of nursing quality in clinical drug trials. It will also clarify how nurses contribute to subjects' safety.